Soil micromorphology at the Viking-Age ring-fortress of Borgring, Denmark: Analysis of samples from the East, North and South Gateways - Sulas, Federica; Kristiansen, Søren M (AU Library Scholarly Publishing Services, 2020)
This report presents the results of soil micromorphological analysis of samples from archaeological deposits uncovered by excavations at Viking-age site of Borgring, on the island of Zealand in eastern Denmark. The study of thin sections has identified different microstratigraphic units in the deposits sampled at the gatesways to the fortress. These suggests accumulation of (colluvial) material mixed with anthropic waste before both the rampart construction and the burning of the wooden gateway structure. The burnt horizon identified in thin section is indicative of rapid and in situ fire. At the top of the sequence, another deposit of (colluvial) material exhibits mini-mal anthropic signature. All in all, this deposit might be reflecting a low-energy, slow soil build-up associated with the presence of animals and people in this landscape after the ring fortress was abandoned.